Castleman disease in children: diagnosis and treatment - Hung, Dinh Viet; Thao, Nguyen Thi Thu; Duc, Le Tho; Tuan, Nguyen Minh; Hieu, Dao Trung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: We describe the experiences in diagnosis and results of treatment in pediatric Castleman disease. Method: Serial case reports. Result: From 2016 to 2019, we had 7 cases of pediatric Castleman disease: 3 boys and 4 girl. The median age at diagnosis was 147 months (121-173 months). Clinical manifestations were found in five cases. They were all unicentric Castleman disease (6 abdominal mass, one left infraclavicular mass). All patients were operated with postoperative period uneventful. The median time of postoperative follow up was 22.7 months (11-53 months) with no signs of relapse. Conclusions: Pediatric Castleman disease is a rare benign lymph node hyperplasia, it can be localised or disseminated. Operation is the treatment of choice for localised Castleman disease.